THE TEACHERS’ TECHNIQUES IN PROVIDING CORRECTIVE FEEDBACK ON STUDENTS’ PRONUNCIATION ERROR - Razali, Khairil; Husna, Nurul (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2018)
This research aimed to analyse the teachers’ implementation of corrective feedback and to identify the types of corrective feedback provided by teachers on students’ pronunciation errors in the classroom. The writer conducted the research at MAS Darul Ulum Banda Aceh. The participants of the research were 1st and 2nd year teachers. The data was collected by doing observations in X and XII classes. The writer found that each of both teachers only used 3 kinds of corrective feedback. The first teacher used recast and metalinguistic while the second teacher used elicitation and clarification request. However, both teachers shared the type of explicit feedback. There are 6 types of corrective feedback proposed by Lyster and Ranta (1997): recast, metalinguistic, clarification request, elicitation, explicit and repetition. The use of each types was different in percentage.